2016
DOI: 10.1589/jpts.28.2055
|View full text |Cite
|
Sign up to set email alerts
|

The effect of virtual reality-based eccentric training on lower extremity muscle activation and balance in stroke patients

Abstract: [Purpose] The purpose of this study was to examine the effect of virtual reality-based eccentric training on lower extremity muscle activity and balance in stroke patients. [Subjects and Methods] Thirty stroke patients participated, with 15 patients allotted to each of two eccentric training groups: one using a slow velocity (group I) and one using a fast velocity (group II). The virtual reality-based eccentric training was performed by the patients for 30 minutes once a day, 5 days a week, for 8 weeks using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
6
0
3
Order By: Relevance
“…Several studies demonstrated that this treatment enriched by reinforced feedback in a virtual environment (RFVE) may be more effective than TR to improve the motor function of the upper limb after stroke [31,32]. In our study, the use of a VR-based system, together with a motion capture tool, allowed us to modify the artificial environment with which the patient could interact, exploiting some mechanisms of motor learning [33,34], thus allowing greater flexibility and effective improvement in task learning. is system has been highly successful in the functional recovery of the hemiparetic upper extremity [31,[33][34][35][36], but its combined effect with TR on the LE has not yet reported conclusive data [37].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies demonstrated that this treatment enriched by reinforced feedback in a virtual environment (RFVE) may be more effective than TR to improve the motor function of the upper limb after stroke [31,32]. In our study, the use of a VR-based system, together with a motion capture tool, allowed us to modify the artificial environment with which the patient could interact, exploiting some mechanisms of motor learning [33,34], thus allowing greater flexibility and effective improvement in task learning. is system has been highly successful in the functional recovery of the hemiparetic upper extremity [31,[33][34][35][36], but its combined effect with TR on the LE has not yet reported conclusive data [37].…”
Section: Introductionmentioning
confidence: 96%
“…In our study, the use of a VR-based system, together with a motion capture tool, allowed us to modify the artificial environment with which the patient could interact, exploiting some mechanisms of motor learning [33,34], thus allowing greater flexibility and effective improvement in task learning. is system has been highly successful in the functional recovery of the hemiparetic upper extremity [31,[33][34][35][36], but its combined effect with TR on the LE has not yet reported conclusive data [37]. e continuous supply of feedback during voluntary movement makes it possible to continuously adjust contractile activity [38], thus mitigating increments in spasticity and cocontraction processes of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…In the domain of motor-rehabilitation, EMG-data can be of particular importance. It can be used to demonstrate the basic effectiveness of the system by showing that users of the application really activate targeted muscles (Park et al, 2016;Drolet et al, 2020). This is of special interest when impairments do not allow visible movement of the target-limb (Patel et al, 2015).…”
Section: Physical Therapymentioning
confidence: 99%
“…In the study by Fernandez-Gonzalo et al [13], 32 subjects with chronic stroke participated in eccentric overload flywheel resistance training for 12 weeks with results showing significantly improved balance and gait performance in the training group. In the study by Park et al [14], 30 chronic stroke participants undertook ECT at different velocities for 8 weeks with results showing improved muscle activation and static balance (limits of stability) at low velocities.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies focused only on functional performance abilities such as balance and gait after muscle contraction training, and there are few studies focusing on muscle characteristics [13,14]. Even if the characteristics of muscle had been analyzed, they were analyzed only by elec-trical signals from the skin surface, such as surface electromyography [14]. Therefore, there have been no studies on the effects of ECT and CCT on the muscle architecture and characteristics of persons affected by stroke.…”
Section: Introductionmentioning
confidence: 99%